Peningkatan kemampuan analisis energi dan sumber energi melalui penerapan model pembelajaran Reading – Concept Map – Somatic Auditory Visualization Intellectual peserta didik kelas iv sekolah dasar - Sawitri, Rina Susi; Kurniawan, Sandra Bayu; Sularmi, Sularmi (Didaktika Dwija Indria, 2019)
The research’s purpose is to improve the analysis ability of energi and energi source through the use of learning models Reading – Concept Map – Somatic Auditory Visualization Intellectual (Remap-SAVI) in class IV SDN Bratan 2 Surakarta 2018/2019 school year. This research is a Classroom Action Research (CAR) which consisted of 2 cycles, each cycle consisting of 2 meetings. The subject of this research are the 30 of class IV SDN Bratan 2 Surakarta, comprising 17 male students and 13 female students. This study uses observational techniques, interviews, documentation, and tests. Data analysis using interactive data analys with step of data reduction, data presentation, and conclusions. The data validity test techniquw uses content validity and triangulation. The result of this research showed that the initial pre-action test score were 57 with classical completeness of 0%, increased in the first cycle by 64 with classical completeness of 23%, then in second cycle it increased significantly to 77 with classical completeness of 83%. Based on the result of the study, it can be concluded that through the application of the Remap-SAVI learning model can improve the analysis ability of energi and energi source in class IV SDN Bratan 2 Surakarta 2018/2019 school year.Keywords: Reading – Concept Map – Somatic Auditory Visualization Intellectual (Remap-SAVI), analysis ability